On The Effect Of Axial Dispersion In The Numerical Simulation Of Fast Cycling Adsorption Processes - C. Y. Soo , C. Y. Soo; Y. L. Lai , Y. L. Lai; T. G. Chuah , T. G. Chuah; S. Mustapha , S. Mustapha; T. S. Y. Choong, T. S. Y. Choong (Penerbit UTM Press, 2005)

(untitled)
The Effects Of Axial Dispersion In The Numerical Simulation Of Fast Cycling Adsorption Processes Were Studied. The Main Objectives Are: (1) To Re-Examine The Observation Of Alpay [1] On The Effect Of Axial Dispersion On The Oxygen Purity For A 1.0 M Column, And (2) To Investigate Numerically The Effect Of Axial Dispersion On The Oxygen Purity And Cycle-Averaged Feed Flow Rate Of An Ultra Rapid Pressure Swing Adsorption (URPSA) Process, Which Employed A Column Of 0.2 M In Length. The Linear Driving Force (LDF) Model Was Employed To Model The Mass Transfer Within The Adsorbent Particles. Numerical Simulation Was Carried Out By Discretising The Partial Differential Equations (Pdes) In The Space Domain To A System Of Ordinary Differential Equations (Odes), Using The Method Of Orthogonal Collocation (OC). The Odes Were Then Integrated Using A Subroutine From IMSL FORTRAN Library, Which Is Suitable For The Integration Of Stiff Odes. For Alpay’s Experimental Conditions, Unphysical Numerical Results Were Observed For An Axial Dispersion Coefficient Predicted By Langer’s Correlation. However, No Such Numerical Difficulties Were Encountered For An URPSA Process. Our Numerical Simulations Showed A Reduction Of Up To 10 Percentage Points When Values Of Axial Dispersions Were Increased. The Axial Dispersion Was Found To Have No Effect On The Cycle-Averaged Feed Gas Rate. Future Works Are Deemed Necessary To Device Suitable Strategy To Overcome The Numerical Difficulties Encountered Here.